Analisis Kinerja Keuangan Perusahaan dengan Menggunakan Altman Z Score dan Pengaruhnya Terhadap Harga Saham - Salsabila, Nadia Bella; Wahyudi, Wahyudi (EQUITY: Jurnal Ekonomi, Manajemen, Akuntansi, 2019)
This research is a quantitative research that aims to analyze company’s  inancial performance using Altman Z Score and also to determine the effect of the Altman Z Score variable on stock prices. The population in this study are consumer goods industry companies in 2016-2017 which are listed on the Indonesia Stock Exchange (IDX). The samples taken were 72 companies with purposive sampling method. The analysis technique used is Multiple Linear Regression Analysis with IBM SPSS 23 program and a significance level of 5% (0.05). The results of this study indicate that (1) Z score of 72 samples of companies listed on the Indonesia Stock Exchange (IDX) in 2016 2017 Obtained 4 companies in the unhealthy category, 9 companies in the gray area category (unsound), and 59 companies in the healthy category (2) RETA, EBITA, and BVEBVTL variables affect stock prices while WCTA and Z Score variables do not affect stock prices.